2017
DOI: 10.2196/jmir.7068
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Health and the Internet: Cross-Sectional Study of Online Preferences Among Adolescents

Abstract: BackgroundThe Internet is widely used by adolescents for sexual health information and bears the potential to increase knowledge and positively affect behavior.ObjectiveThe objective of this study is to assess students’ preferences when looking for sexual health information online.MethodsWe conducted a cross-sectional survey among ninth grade students in a convenience sample of 13 secondary schools in Berlin, Germany. During a regular school period, participants were requested to rate the importance they attri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 36 publications
0
39
1
2
Order By: Relevance
“…It was demonstrated that adolescents were ill-informed on the important issue of emergency contraception [ 47 ]. Furthermore, adolescents’ preferences regarding online sexual health resources were assessed [ 48 ]. The survey was conducted throughout the year 2012 in grade nine of secondary schools in Berlin.…”
Section: Methodsmentioning
confidence: 99%
“…It was demonstrated that adolescents were ill-informed on the important issue of emergency contraception [ 47 ]. Furthermore, adolescents’ preferences regarding online sexual health resources were assessed [ 48 ]. The survey was conducted throughout the year 2012 in grade nine of secondary schools in Berlin.…”
Section: Methodsmentioning
confidence: 99%
“…Mayoritas remaja menyatakan fitur yang ada pada website sangat mudah digunakan, mudah untuk diakses, kemudahan tersebut dilihat dari tahapan penggunaan website (56%), pengantar video (63%), langkah-langkah (56%), kisah sukses (56%), fakta dan kiat (81%), templet (73) sehingga remaja merasa puas (10,18). Remaja juga mengatakan bahwa website mempunyai tata letak informasi yang jelas (19) . Penggunaan mhealth lebih mudah dan lebih cepat dalam melakukan pengujian terhadap status infeksi Jurnal Penelitian Kesehatan Suara Forikes ------http://forikes-ejournal.com/index.php/SF menular seksual remaja (15) .…”
Section: Respon Terhadap Mhealth Dalam Peningkatan Kesehatan Reprodukunclassified
“…On this subject, some of the proposals for the future of eHealth are to improve users' health and eHealth literacy [10][11][12], to procure more health care providers' implication in eHealth development [13], to improve usability of eHealth [14,15], and to investigate eHealth's effectiveness [16]. We decided to develop and evaluate, from the point of view of the users, an open and free-access eHealth pediatric website for parents which contained 338 topics about pediatric symptoms, illnesses, and well-child care.…”
Section: Introductionmentioning
confidence: 99%